Changes in the social discount rate and its impact on the approval rate of rural drinking water projects recommended for execution - Cabrera, Nelson (Journal Studies of Public Policy, 2019)
This paper reviews the theoretical aspects associated with the existing approaches and methodologies to determine the value of the Social Discount Rate and the implications for changing its value in Rural Potable Water projects in Chile. The levels of Elasticity in the Project Approval Rate are estimated and evaluated in a context of decreasing discount rate, as recorded in the last two decades. The results suggest the absence of significant levels of elasticity in the Project Approval Rate. The analysis is performed considering the use of the exponential discount factor, traditionally used by economic theory for the evaluation of projects, as well as the use of discount factors based on decreasing (hyperbolic) discount rates. A sample of 42 Rural Drinking Water projects belonging to the provinces of the Bio Bio Region was used in the study.